1974
DOI: 10.1107/s0567740874006431
|View full text |Cite
|
Sign up to set email alerts
|

BaWO4-II (a high-pressure form)

Abstract: Abstract. Monoclinic, P21/n, a = 13.159 (12), b = 7.161 (3), c=7.499 (6) A, /?=93.76 (5) °. Z=8. Om=7"17, Dx= 7"26 g cm -3. Crystals were synthesized under high pressure at high temperature. The structure has no direct resemblance either to the scheelite-or to the wolframitetype. It consists of densely packed layers of WO6 octahedra, which are connected by edge-and corner-sharing; barium atoms are located between them. The coordination number of the barium atoms has increased in comparison with the structure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
3

Year Published

1976
1976
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 3 publications
2
31
1
3
Order By: Relevance
“…• C [4,5]. Later, the monoclinic BaWO 4 -II has also been obtained at about 10 GPa and room temperature [6,7].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…• C [4,5]. Later, the monoclinic BaWO 4 -II has also been obtained at about 10 GPa and room temperature [6,7].…”
Section: Introductionmentioning
confidence: 91%
“…88, Z = 4) plays a significant role in mineralogy, materials science, and geoscience. Under ambient conditions, a large number of ABO 4 -type tungstates and molybdates crystallize in this structure [1]. Many other ABO 4 compounds with zircon (I4 1 /amd), monazite (P2 1 /n), and CrVO 4 -type structures (Cmcm) transform to the scheelite polymorph at high pressure [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher pressure, new phases were found in PbWO4 (Chang, 1971) and BaWO 4 (Fujita, Yamaoka & Fukunaga, 1974). The high-pressure form of BaWO 4 (BaWO4-II) has a characteristic dense structure (Kawada, Kato & Fujita, 1974), and that of PbWO 4 is * A list of structure factors has been deposited with the British Library Lending Division as Supplementary Publication No. SUP 32000 (11 pp.).…”
mentioning
confidence: 99%
“…Since the cell dimensions and space group indicated that PbWO4-11I is probably isomorphous with the high-pressure phase BaWO4-1I (Kawada, Kato & Fujita, 1974), the fractional coordinates found there were used as the starting point for full-matrix leastsquares refinement. The temperature factors of the O atoms were refined isotropically.…”
Section: National Physical Researchmentioning
confidence: 99%